The Charity Values within Islamic Law of Inheritance in Malang: Maqāṣid al-Sharī’ah and Social Construction Perspectives - Mahmudi, Zaenul; Zenrif, M. Fauzan; Haris, Abdul; Mustafa, Ahsin Dinal; Yasin, Noer (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Islamic principles regarding zakat in general are closely related to the issue of wealth which must be distributed to the needy and poor as well as groups that have been determined by Islamic law. This article aims to discuss the principles of charity in the distribution of inheritance by analyzing the views of ulama and intellectuals in Malang City, East Java. This study is socio-legal research using the theory of maqāṣid al-sharī'ah and social construction. Data was obtained from document study sources in the form of opinions of tafsir and fiqh scholars, journal articles and books related to the discussion. The informants interviewed were NU member, Muhammadiyah, MUI, and academics. The results of this study revealed that: first, based on the principles of justice and benefit, as the general elements of maqāṣid, in the inheritance verses, there is a command to set aside inherited property for the needy from the group of distant relatives, orphans, and the poor (al-Nisa: 8) and to help the heirs who are less able (al-Nisa: 9) as maqāṣid al-kulli. Second, based on social construction, at the externalization stage, the ulema and Muslim community in the city of Malang practice the Islamic charity by setting aside inherited property for the poor, the needy, and orphans in various forms such as slametanfor the deceased, endowments for orphanages, and donations to educational institutions, as well as giving some of the inherited property to their less fortunate relatives. Muslim community simultaneously objectifies the Islamic charity so that the Islamic charity becomes an objective reality in the city of Malang, although the Muhammadiyah community does not observe slametan. The internalization of the construction of Islamic charity as a final stage is understood by internalizing the verses of Islamic charity as the beliefs and teachings that must be implemented in society.